The medium-term impact of the primary education stipend in rural Bangladesh - Baulch, Bob (International Food Policy Research Institute, 2010)
This paper investigates the long-term impact of Bangladesh's Primary Education Stipend (PES) program on a range of individual and household welfare measures using a unique longitudinal study spanning the years 2000 to 2006. Using covariate and propensity score matching and difference-in-difference methods, the program is shown to have negligible impacts on school enrollments, household expenditures, calorie consumption, and protein consumption. At the individual level, the PES has a negative impact on grade progression, especially among boys from poor households who are ineligible to receive stipends at the secondary level. The program does, however, lead to improvements in height for age among girls and body mass index among boys. Nonetheless, the impacts of the PES are remarkably small for a program of its size. Poor targeting combined, in particular the program's limited coverage and lack of geographical targeting, plus the declining real value of the stipend are the most plausible reasons for this lack of impact.